Evaluating the effect of COVID-19 pandemic on the psychological health of young adults in India - Alka Sabharwal; Babita Goyal; Vibha S Chauhan; Lalit Mohan Joshi; Vaibhav Goyal (International Journal of Public Health Science (IJPHS), 2023)
COVID-19 pandemic has affected the mental health of individuals, particularly young adults. Using the ‘strength and difficulty questionnaire 17+ extended version’, we studied the severity of psychological problems and the resultant distress in young adults; the relationship between the ‘difficulty’ and ‘impact’ scores; and the effect of distress in terms of a number of day-to-day activities affected during a pandemic. Data was collected from 743 college/university students (December 2020-February 2021) in India. Descriptive, relative frequencies, and nonparametric tests are applied here. Females were facing more psychological behavioral problems as compared to males as the p-value is less than 0.001. Males with age<20 years were least affected by COVID-19. Day-to-day activities are affected by almost 45% of young adults because of distress. ‘difficulty’ and ‘impact’ severity bands were significantly different from the previous standard proportions. No significant association was there between ‘difficulty’ and ‘impact’ scores (p-value<0.001). 53% of those contracting COVID-19 had severe distress as against 45% of those who did not. 46% of the respondents were in the ‘abnormal’ category and 59 out of 327 were facing ’a great deal’ problems in more than two areas.